Hereditary predisposition of water voles (Arvicola amphibius L.) to seizures in response to handling - G. G. Nazarova; L. P. Proskurnyak (Вавиловский журнал генетики и селекции)
Finding out the hereditary predisposition to seizures in response to specific external stimuli is important for understanding the causes of epileptiform conditions, developing new methods for their prevention and therapies. In the water vole, individuals with convulsive seizures are found both in natural and laboratory conditions. The data of long-lasting maintenance and breeding of water voles in vivarium conditions were analyzed in order to establish a hereditary predisposition to convulsive seizures, and the influence of sex and age on their development. In the vivarium, seizures are provoked by handling and are observed in 2.4 % of voles caught in the natural population with cyclic fluctuations in abundance. Seizures are observed more often in individuals caught in the phases of decline and depression of abundance than in individuals caught in the phases of rise or peak. Convulsive states are probably an element of adaptive behavior formed in the predator-prey system. In natural conditions, individuals predisposed to convulsive seizures may have a selective advantage when under increasing pressure from predators. Convulsive seizures in response to handling were noted in 29.8 % of descendants of captive-bred water voles. The proportion of such individuals increased significantly if one or both parents had convulsive states, which indicates the presence of a hereditary predisposition to seizures. In parent–offspring pairs, a significant correlation was found between the average age of onset of the first seizures in parents and their offspring, r = 0.42, p < 0.01. The minimum age of registration of seizures in the water vole is 39 days, the maximum is 1105 days, and the median is 274 days. Predisposition to seizures is not related to sex. Genes that control the occurrence of seizures have a pleiotropic effect on life span, since individuals with seizures live longer in vivarium conditions than individuals with a normal phenotype. The water vole can serve as a suitable model object for studying the nature of convulsive states and the evolution of longevity.